The Rise and Fall of Sunni-Shia Relations in Indonesia: The in-Between Theology, Political-Economics, and Da’wah - Asmana, Azis; Mubarok, Wijdan Khoirul Mubtadi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study discusses the dynamics of the relationship between Sunnis and Shiites in Indonesia, which are sometimes tense, but generally harmonious. This study is qualitative-research using a literature review method. To sharpen the analysis of the discussion of the dynamics of Sunnis-Shiites, interdisciplinary research is used in the study of religions. The results of this study indicate that the main factor causing tension between Shiites vis-Ã -vis Sunnis is due to the doctrine of the Imamate which is the belief of the Shiites themselves. This doctrinal difference is what gives rise to other elementary factors such as politics and economics. That the elements of doctrine, politics and economics make the relationship between Sunnis and Shiites in Indonesia even more complicated. The three are intertwined in such a way that the Sunni-Shiite conflict develops in various regions of Indonesia. However, this study also shows a relatively harmonious relationship process between Sunnis and Shiites in various regions of Indonesia. The harmonization process between the two camps with different ideologies occurs at the grassroots level. This study recommends the process of strengthening cultural da’wah as one of the harmonization strategies among religious communities in Indonesia.